The Opportunistic Pathogen Vibrio vulnificus Produces Outer Membrane Vesicles in a Spatially Distinct Manner Related to Capsular Polysaccharide - Hampton, Cheri M.; Guerrero-Ferreira, Ricardo C.; Storms, Rachel E.; Taylor, Jeannette V.; Yi, Hong; Gulig, Paul A.; Wright, Elizabeth R. (Frontiers in Microbiology, 2017)
Vibrio vulnificus, a bacterial species that inhabits brackish waters, is an opportunistic pathogen of humans. V. vulnificus infections can cause acute gastroenteritis, invasive septicemia, tissue necrosis, and potentially death. Virulence factors associated with V. vulnificus include the capsular polysaccharide (CPS), lipopolysaccharide (LPS), flagellum, pili, and outer membrane vesicles (OMVs). The aims of this study were to characterize the morphology of V. vulnificus cells and the formation and arrangement of outer membrane vesicles (OMVs) using cryo-electron microscopy. Cryo-electron microscopy and cryo-electron tomography imaging of V. vulnificus strains grown in liquid cultures revealed the presence of outer membrane vesicles (diameters of ~45 nm for wild-type, ~30 nm for the unencapsulated mutant, and ~50 nm for the non-motile mutant) in log-phase growth. Production of OMVs in the stationary growth phase was limited and irregular. The spacing of the OMVs around the wild-type cells was in regular, concentric rings. In wild-type cells and a non-motile mutant, the spacing between the cell envelope and the first ring of OMVs was ~200 nm; this spacing was maintained between subsequent OMV layers. The size, arrangement, and spacing of OMVs in an unencapsulated mutant was irregular and indicated that the polysaccharide chains of the capsule regulate aspects of OMV production and order. Together, our results revealed the distinctive organization of V. vulnificus OMVs that is affected by expression of the capsular polysaccharide.